1973
DOI: 10.1007/bf00022640
|View full text |Cite
|
Sign up to set email alerts
|

Anther culture of Solanum tuberosum L.

Abstract: Embryoid formation was induced in pollen of Solanum tuberosum, cv . Pentland Crown, Maris Piper and Record, by culturing anthers at or just prior to the first pollen mitosis . The composition of the medium was not critical in respect of either nutrients or hormones . In the presence of relatively high hormone levels, callus formation also occurred from somatic tissues of the anthers .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

1974
1974
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(23 citation statements)
references
References 7 publications
(7 reference statements)
1
21
0
1
Order By: Relevance
“…Seasonal variations in anther response were reported for a number of species including Solanum tuberosum (4), Hordeum vulgare (2), and Triticum aestivum (17). For B. napus, controlled studies of the effects of growth temperature, light intensity, and light duration on anther culture response showed that embryo production could be significantly increased by growing the donor plants at a low (1 5C) temperature (3,11,12) and high light (12,20).…”
mentioning
confidence: 99%
“…Seasonal variations in anther response were reported for a number of species including Solanum tuberosum (4), Hordeum vulgare (2), and Triticum aestivum (17). For B. napus, controlled studies of the effects of growth temperature, light intensity, and light duration on anther culture response showed that embryo production could be significantly increased by growing the donor plants at a low (1 5C) temperature (3,11,12) and high light (12,20).…”
mentioning
confidence: 99%
“…In only a few cases (5,10,14,20) has plant regeneration been achieved from excised tissues other than shoot tips. Recently, however, there has been definite progress toward the development of an in vitro regeneration system from single cells.…”
mentioning
confidence: 99%
“…4-5). In any case the cell walls were not as distinct as those observed in the case of Nicotiana (NITSCH, 1972;SUNDERLAND, 1971), Datura (IYER & RAINA, 1972) and in vitro formed embryoids of Solarium (DUNWELL & SUNDERLAND, 1973).…”
Section: Resultsmentioning
confidence: 90%